Analisis Kesesuaian Kompetensi Manajerial Dosen Perguruan Tinggi X - Sri Hayati; Nurhikmah Nurhikmah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Competent human resources will support the achievement of the university's vision and mission, while incompetent human resources will hinder the achievement of short, medium and long-term work targets, so that in the end it will hinder universities from developing and may even experience a decline. Lecturers as the spearhead of academic activities are faced with high job demands, apart from carrying out teaching, community service, and research, some lecturers also occupy structural positions which of course require managerial competence in order to carry out their duties optimally. This study aims to see the suitability of the competencies possessed by lecturers as structural position holders with the competencies required for the position. This study uses a competency assessment method consisting of tests and non-tests. The test form of assessment uses the CFIT, DISC, Kraeplin, Graphic and Warteg tests, while the non-test form uses interviews, observation, case studies and Leaderless Group Discussion. The subject of this study was a lecturer who served as head of the study program, male, 50 years old. The research results show that Mr. M has competencies that meet the requirements, namely integrity, interpersonal skills, customer focus, building business partnerships and driving execution. Meanwhile, the 4 competencies that still need to be improved to fulfill the position requirements as chair of the study program, namely change leadership, achievement orientation, empowering and innovation creativity. Steps that can be taken to improve these competencies include job assignment and mentoring methods.